Dirhodium Coordination Polymers for Asymmetric Cyclopropanation of Diazooxindoles with Olefins: Synthesis and Spectroscopic Analysis. Issue 8 (13th August 2020) - Li, Zhenzhong; Rösler, Lorenz; Herr, Kevin; Brodrecht, Martin; Breitzke, Hergen; Hofmann, Kathrin; Limbach, Hans‐Heinrich; Gutmann, Torsten; Buntkowsky, Gerd
Abstract: A facile approach is reported for the preparation of dirhodium coordination polymers [Rh2 (L1)2 ]n (Rh2 ‐L1) and [Rh2 (L2)2 ]n (Rh2 ‐L2; L1= N, N' ‐(pyromellitoyl)‐ bis ‐ L ‐phenylalanine diacid anion, L2= bis‐N, N'‐ ( L‐ phenylalanyl) naphthalene‐1, 4, 5, 8‐tetracarboxylate diimide) from chiral dicarboxylic acids by ligand exchange. Multiple techniques including FTIR, XPS, and 1 H→ 13 C CP MAS NMR spectroscopy reveal the formation of the coordination polymers. 19 F MAS NMR was utilized to investigate the remaining TFA groups in the obtained coordination polymers, and demonstrated near‐quantitative ligand exchange. DR‐UV‐vis and XPS confirm the oxidation state of the Rh center and that the Rh‐single bond in the dirhodium node is maintained in the synthesis of Rh2 ‐L1 and Rh2 ‐L2. Both coordination polymers exhibit excellent catalytic performance in the asymmetric cyclopropanation reaction between styrene and diazooxindole. The catalysts can be easily recycled and reused without significant reduction in their catalytic efficiency. Abstract : Polymer power : Stable dirhodium coordination polymers for asymmetric cyclopropanation can be synthesized in a simple route involving ligand exchange. Almost quantitative exchange is obtained, as confirmed by 19 F MAS NMR. The as‐obtained coordination polymers are efficient heterogenous catalysts in the reaction of diazooxindole with styrene to form spiro‐cyclopropyloxindole, an important structural moiety in medical research of antitumor agents or HIV inhibitors.